Calculation of electron scattering on atomic silver. (29th March 2018) - McNamara, Keegan; Fursa, Dmitry V; Bray, Igor
Abstract: We report on the application of the relativistic convergent close-coupling method to electron scattering from silver atoms. Differential and integrated cross sections are presented for elastic scattering and excitation to a number of low-lying excited states for energies ranging from 0.1 to 200 eV. The total and ionisation cross sections and elastic spin asymmetry parameters are also presented, and we find potentially large relativistic effects for elastic scattering at low energies. The results are compared with experiments where available, and somewhat variable agreement is found.